Isaiah Dunn is my hero - Baptist, Kelly J. (Yearling, 2021)
After his father's death, Isaiah feels that he is now the man of the house and it is his responsibility to take care of his Mama and little sister. When things get really tough at home, Isaiah depends on the stories in his daddy's journal in order to find his way out of the darkness.